Literature as Politics, Politics as Literature: Essays on the Ancient Near East in Honor of Peter Machinist - Avigdor Hurowitz, Victor; Cohen, Yoram; Dubovský, Peter; Fales, Frederick Mario; Fleming, Daniel E.; Frahm, Eckart; Glassner, Jean-Jacques; Goldstein, Ronnie; Hallo, William W.; Halpern, Baruch; Hamilton, Mark W.; Huddlestun, John R; et al. (Penn State University Press, 2021)
Frontmatter -- Contents -- Publisher’s Note -- Peter Machinist -- Bibliography of Peter Machinist -- Fearful Symmetry: The Poetics, Genre, and Form of Lines 109–118, Tablet I in the Poem of Erra -- Menahem’s Reign Before the Assyrian Invasion (2 Kings 15:14–16) -- Ethnicity in the Assyrian Empire: A View from the Nisbe, (I): Foreigners and “Special” Inner Communities -- David and the Ark: A Jerusalem Festival Reflected in Royal Narrative -- Creation and the Divine Spirit in Babel and Bible: Reflections on mummu in Enūma eliš I 4 and rûaḥ in Genesis 1:2 -- Niṣirti bārûti: une autre approche -- NB Administrative Terminology and Its Influence in Biblical Literature: Hebrew ארח -- Biblical and Ancient Near Eastern Literatures: A General Introduction -- Between Elective Autocracy and Democracy: Formalizing Biblical Constitutional Theory -- Prosperity and Kingship in Psalms and Inscriptions -- Redactors, Rationalists, and (Bloodied) Rivers: Some Comments on the First Biblical Plague -- “An Heir Created by Aššur”: Literary Observations on the Rassam Prism (A) of Ashurbanipal -- Literary-Political Motifs in the Assyrian Royal Inscriptions: Measuring Continuity versus Change -- Of Bears and Men: Thoughts on the End of Šulgi’s Reign and on the Ensuing Succession -- A Hidden Anti-David Polemic in 2 Samuel 6:2 -- The Prophet and the Augur at Tušḫan, 611 b.c. -- Assyria and Judean Identity: Beyond the Religionsgeschichtliche Schule -- Psalm 22:16 and Its Sumerian and Akkadian Analogues -- Do Ideas Travel Lightly?: Early Greek Concepts of Justice in Their Mediterranean Context -- The Rod that Smote Philistia: Isaiah 14:28–32 -- Errant Oxen Or: The Goring Ox Redux -- Jephthah: Chutzpah and Overreach in a Hebrew Judge -- The Remembrance of Kings Past: The Persona of King Ibbi-Sin -- Hittite Gods in Egyptian Attire: A Case Study in Cultural Transmission -- How Did Šulgi and Išbi-Erra Ascend to Heaven? -- “War Crimes” in Amos’s Oracles Against the Nations (Amos 1:3–2:3) -- Grammar and Context: Enki & Ninhursag ll. 1–3 and a Rare Sumerian Construction -- Towards a Biography of Kish: Notes on Urbanism and Comparison -- Index of Authors -- Index of Scripture